Temporal branch of facial nerve: a normative study of nerve conduction - Silva,Paula Fabiana Sobral da (2010)
The temporal branch of the facial nerve is particularly vulnerable to traumatic injuries during surgical procedures. It may also be affected in clinical conditions. Electrodiagnostic studies may add additional information about the type and severity of injuries, thus allowing prognostic inferences. The objective of the present study was to develop and standardize an electrophysiological technique to specifically evaluate the temporal branch of the facial nerve. METHOD: Healthy volunteers (n=115) underwent stimulation of two points along the nerve trajectory, on both sides of the face. The stimulated points were distal (on the temple, over the temporal branch) and proximal (in retro-auricular region). Activities were recorded on the ipsilateral frontalis muscle. The following variables were studied: amplitude (A), distal motor latency (DML) and conduction velocity (NCV). RESULTS: Differences between the sides were not significant. The proposed reference values were: A >0.4 mV, DML <3.9 ms and NCV >40 m/s. Variation between hemifaces should account for less than 60% for amplitudes and latency, and should be inferior to 20% for conduction velocity. CONCLUSION: These measurements are an adequate way for proposing normative values for the electrophysiological evaluation of the temporal branch.